Revision of Smart Street Lighting LED - Rodríguez Patarroyo, Diego Julián; Cely Garzón, Iván Felipe; Letrado Forero, Cristhian Alexander (Ingeniería Solidaria, 2019)
Introduction: This Literature Review article is the result of a research on the current situation of smart public lighting systems with light-emitting diode (LED) technology in cities around the world. Problem: How convenient is it to use smart public lighting system with LED luminaires? Objective: To review the context of smart public lighting with LED technology. Methodology: Within this project, a lit review was conducted with more than 50 academic articles found in different databases such as: IEEE Xplore, Scopus, ScienceDirect etc. The selection criteria of the information followed the revision of articles from 2006 to 2018, and also, took into account their installation and performance in different cities and places of the world. Furthermore, articles on polluting and inefficient technologies were excluded. Conclusion: Considering the current context in which LED smart public lighting is, it is more likely to be implemented in the future. Results: Smart LED street lighting systems are more efficient in energy use, leads to savings in costs in medium terms, and finally, present a lower environmental impact compared to conventional lighting systems. Limitations: The review focuses on energy efficiency and economic aspects, not on social aspects. Originality: Smart LED public lighting systems have been researched within the economic and energy efficiency context.